C‐reactive protein levels in patients with amyotrophic lateral sclerosis: A systematic review. Issue 3 (24th February 2022) - Kharel, Sanjeev; Ojha, Rajeev; Preethish‐Kumar, Veeramani; Bhagat, Riwaj
Abstract: Introduction: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease affecting cortical and spinal motor neurons. There is a lack of optimal biomarkers to diagnose and prognosticate the ALS patients. C‐reactive protein (CRP), an inflammatory marker, has shown promising results in ALS patients. Materials and methods: PubMed, Embase, and Google Scholar databases were searched from 2000 to June 1, 2021 for suitable studies showing the relationship between CRP and ALS. The concentration of CRP levels was assessed between ALS patients and controls. Further, end outcomes like ALS functional rating scale (ALSFRS‐R), survival status, and mortality risks were assessed in relation to CRP levels. Results: Eleven studies including five case–control, five cohorts, and one randomized control study were assessed. There were 2785 ALS patients and 3446 healthy controls. A significant increment in CRP levels among ALS patients in comparison with healthy controls were seen in most of the studies. ALSFRS‐R and disease progression were found to be significantly correlated with CRP levels. Overall accuracy of CRP in CSF was 62% described in a single study. Conclusion: Although CRP has shown promise as a prognostic biomarker, extensive cohort studies are required to assess its prognostic value and accuracy in diagnosing ALS taking into account the confounding factors. Abstract : Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease that affects cortical and spinal motor neurons. The underlying neuroinflammatory process in the pathogenesis of ALS has researchers interested in C‐reactive protein (CRP) as a possible disease biomarker. We used a comprehensive review to investigate the link between CRP levels and disease progression in ALS patients versus healthy controls. The concentration of CRP levels was assessed between ALS patients and controls. Further, end outcomes like ALS functional rating scale, survival status, and mortality risks were assessed in relation to CRP levels.